Contract duration and relationship-specific investments: Empirical evidence from coal markets - Joskow, Paul L. (American Economic Review, 1987)
This paper examines empirically the importance of relationship investments in determining the duration of coal contracts negotiated between coal suppliers and electric utilities, using data for 277 coal contracts. For each contract, measures of the duration of contractual commitments agreed to by the parties at the contract execution stage and measures of the importance of relationship specific investments are developed. The results provide strong support for the view that buyers and sellers make longer commitments to the terms of future trade at the contract execution stage, and rely less on repeated bargaining, when relationship-specific investments are more important. Copyright 1987 by American Economic Association.